PSYCHOLOGICAL MECHANISMS OF COPING BEHAVIOR FACTORS IN ADOLESCENTS - Nosirova Sitorabonu Alisher qizi (American Journals Publishing, 2023)
This article provides a summary of the research conducted in the field of defense mechanisms and coping behavior in adolescents.
Keywords: coping behavior, coping strategy, coping, defense mechanism, problem